2008
DOI: 10.4314/ari.v3i2.40767
|View full text |Cite
|
Sign up to set email alerts
|

Production Of Some Virulence Factors Under Different Growth Conditions And Antibiotic Susceptibility Pattern Of <i>Aeromonas hydrophila </i>

Abstract: The production of some virulence factors under different growth conditions and antibiotic suscept bility pattern of Aeromonas hydrophila were investigated in this s udy. The virulence actors tested on the isolates included haemolytic activity, exopolysaccharide (capsule) and toxin production. Other cell property evaluated was antibiotic resistance. Of the several chemotherapeutants tested, streptomycin had Minimal Inhibitory Concentration (MIC) and Minimal Cidal Concentration (MCC) at 25 µg/ml; flumequine, MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our results were in agreement with these data, with MIC values for cefoxitin of ≤0.5-16 µg/mL and for ceftriaxone of ≤0.25-32 µg/mL. Dibua & Okpokwasili (2006) indicated that MIC of chloramphenicol vs. A. hydrophila was 15 µg/mL, and that of tetracycline -80 µg/mL. Jones et al (1988) reported that the MIC of azithromycin against A. hydrophila was 4 µg/mL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were in agreement with these data, with MIC values for cefoxitin of ≤0.5-16 µg/mL and for ceftriaxone of ≤0.25-32 µg/mL. Dibua & Okpokwasili (2006) indicated that MIC of chloramphenicol vs. A. hydrophila was 15 µg/mL, and that of tetracycline -80 µg/mL. Jones et al (1988) reported that the MIC of azithromycin against A. hydrophila was 4 µg/mL.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike us, Thayumanavan et al (2003) showed a resistance to gentamicin (3.6%). The MIC of gentamicin according to Dibua & Okpokwasili (2006) is 50 µg/mL, of kanamycin -45 µg/mL and of streptomycin -25 µg/mL vs. A. hydrophila. The MIC values obtained in this study for gentamicin (≤1-4 µg/mL) and kanamycin (≤8-16 µg/mL) were lower, and the results for streptomycin -comparable (≤ 32 µg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Ten (10) of the earthworms (P. posthuma) of similar sizes were gently dropped into 20 mg/ml of each ethanolic extract; 20 mg/ml of piperazine; and 20 mg/ml of the control (5% DMF), respectively, in 50 ml conical flask. These were then observed for 24 h for significant behavioral responses (morbidity behaviors) ranging from erratic movement, contraction and relaxation of circular and longitudinal muscles, slower or irregular movement and pale appearance as well as time of killing as described by Dibua and Okpokwasili, (2006).…”
Section: Bioassay and Antihelminthic Activity Of Test Plantmentioning
confidence: 99%